2018
DOI: 10.18203/2349-3933.ijam20180003
|View full text |Cite
|
Sign up to set email alerts
|

Study of clinical profile of tuberculosis patients admitted in respiratory medicine ward at a tertiary care hospital in Marathwada

Abstract: Background: Tuberculosis is one of the most important cause of most of the respiratory diseases. It is estimated that about one-third of the world's population is infected with mycobacterium tuberculosis. It is important to know about the clinical profile of these patients. There are many studies which are done among OPD patients but fewer among indoor patients hence, the current study was planned.Methods: Retrospective study of the patients admitted in the inpatient department of the study area were taken as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…4 The mean age of patients was 33.4 years noted in present study was slightly lower than the mean age 41.17 yrs of the patients observed by Bilagi et al 4 Majority (34.18%) of the patients belonged to the age group of 20-30 years. Similar findings were also noted in the study conducted by Bilagi et al and Ahmed et al 4,7 In the present study, 1811 (75.02%) of the patients had pulmonary involvement while 603 (24.98 %) patients had extra pulmonary involvement. Similarly study by Karir et al at Kolkata observed 33 (41.3%) cases had pulmonary TB, 41 (51.2%) cases had extra-pulmonary TB and 6 (7.5%) had both pulmonary and extra-pulmonary TB.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…4 The mean age of patients was 33.4 years noted in present study was slightly lower than the mean age 41.17 yrs of the patients observed by Bilagi et al 4 Majority (34.18%) of the patients belonged to the age group of 20-30 years. Similar findings were also noted in the study conducted by Bilagi et al and Ahmed et al 4,7 In the present study, 1811 (75.02%) of the patients had pulmonary involvement while 603 (24.98 %) patients had extra pulmonary involvement. Similarly study by Karir et al at Kolkata observed 33 (41.3%) cases had pulmonary TB, 41 (51.2%) cases had extra-pulmonary TB and 6 (7.5%) had both pulmonary and extra-pulmonary TB.…”
Section: Discussioncontrasting
confidence: 62%
“…So, it is important to know the reasons for admission and also the profile of TB patients who get admitted so that we prevent further incidence and for early diagnosis, so, the above study was undertaken. 4 The program aims to achieve universal access to TB services with a treatment success rate of atleast 90%. To achieve this, it is important to examine specific clinical and demographic subgroups who might be at high risk of poor treatment outcomes and to provide special attention to them if needed.…”
Section: Introductionmentioning
confidence: 99%
“…This finding supports the previous finding of pleural involvement (55% and 73%) as the commonest extrapulmonary site among hospitalized patients. 4,18 Diagnosis of tuberculosis remains a major challenge in the developing countries. 19 In 2018, only around half of all reported pulmonary tuberculosis globally were bacteriologically confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports the previous finding of pleural involvement (55% and 73%) as the commonest extrapulmonary site among hospitalized patients. 4 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation